Transmission of lymphocystis disease virus to cultured gilthead seabream, Sparus aurata L., larvae. Issue 6 (20th November 2012) - Cano, I; Valverde, E J; Garcia‐Rosado, E; Alonso, M C; Lopez‐Jimena, B; Ortiz‐Delgado, J B; Borrego, J J; Sarasquete, C; Castro, D
Abstract: The transmission of lymphocystis disease virus (LCDV) to gilthead seabream, Sparus aurata L., larvae was investigated using fertilized eggs from a farm with previous reports of lymphocystis disease. LCDV genome was detected by PCR‐hybridization in blood samples from 17.5% of the asymptomatic gilthead seabream broodstock analysed. Using the same methodology, eggs spawned from these animals were LCDV positive, as well as larvae hatched from them. The presence of infective viral particles was confirmed by cytopathic effects development on SAF‐1 cells. Whole‐mount in situ hybridization (ISH) and immunohistochemistry (IHC) showed the presence of LCDV in the epidermis of larvae hatched from LCDV‐positive eggs. When fertilized eggs were disinfected with iodine, no viral DNA was detected either in eggs (analysed by PCR‐hybridization) or in larvae (PCR‐hybridization and ISH). These results suggest the vertical transmission of LCDV, the virus being transmitted on the egg surface. Larvae hatched from disinfected eggs remain LCDV negative during the endotrophic phase, as showed by PCR‐hybridization, ISH and IHC. After feeding on LCDV‐positive rotifers, viral antigens were observed in the digestive tract, which suggests that viral entry could be achieved via the alimentary canal, and that rotifers can act as a vector in LCDV transmission to gilthead seabream larvae.